PENGARUH PENGELOLAAN MODAL KERJA TERHADAP TINGKAT PROFITABILITAS (ROA) PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI PERIODE TAHUN 2013-2017 - Zakaria Hamzah, Zeze; Ayu Anggitya Rahma , Dian (Economicus, 2019)
The purpose of this research is capital investment in food and beverage companies listed on the Indonesia Stock Exchange in the period 2013-2017. The type of data used in research is quantitative causality. Data samples were taken using purposive sampling method. The results of this study indicate that working capital variables consisting of current ratio, accounts receivable turnover, preparation turnover and simultaneous working capital turnover (together) are significantly related to profitability (ROA). With a partial ratio (ROA) with a sig value of 0.045 <0.05 and a value of t arithmetic 2.097> 2.042 and accounts receivable turnover (ROA) with a sig value of 0.013 <0.05 and a t value of 2.634> 2.042. Inventory turnover and working capital do not affect profitability (ROA). Then from the results of the Beta Standard Coefficient shows the most dominant variable is the current ratio with a value of 0.468. From the regression results in this study the influence of the independent variables amounted to 32.7% while the remaining 67.3% was needed by other factors outside this study.